CEO Social Capital and Entrepreneurial Orientation of the Firm: Bonding and Bridging Effects. (November 2015) - Cao, Qing; Simsek, Zeki; Jansen, Justin J. P.
Prior studies demonstrate the role of various facets of CEOs' individual characteristics in shaping a firm's entrepreneurial orientation (EO). We complement this line of research by theorizing and testing the impact of CEOs' social capital on EO. From an original, multisource survey data set of 122 Chinese technology firms, we find that a CEO's bonding social capital with organizational members from various functional units has an inverted U-shaped relationship with firm EO, while the CEO's bridging social capital with the firm's diverse set of external stakeholders has a positive association with EO. In addition, we find that the relationship between CEO bridging social capital and EO becomes stronger as the firm's environmental instability increases.